The general court of the Agenais revisited: an innovation of the Albigensian Crusade - Taylor, Claire (Brepols, 2018)
The general court of the Agenais is an example of the diverse forms of semi-autonomous regional assemblies which emerged in the high-medieval Languedoc. They were identified and examined most convincingly by Thomas Bisson. However, the origins of the court, identified by Bisson as lying with the Plantagenet rulers of the Agenais in the twelfth century, have been contested since 1986. They are reinterpreted here instead as being thirteenth-century, and as the creation of the Albigensian Crusade (1209-29). In doing this, the early evidence is reconsidered in a new institutional context.